Praktik Childfree di Indonesia: (Studi Terhadap Respon Ormas Islam di Kabupaten Kebumen) - Ahmadrezy Meidina; Mega Puspita (Universitas Negeri Jakarta, 2023)
This article discusses child-free practices in Indonesia. Childfree means an agreement made by husband and wife not to have children during the marriage period. Practices in society are still taboo when you hear the term childfree itself. There is also a small portion of society that is no longer a taboo and has even practiced it, especially among the upper elite. This research is interesting to study because childfree itself is contrary to the purpose of marriage, namely having children and reproductive rights in Islam to enjoy biological relations. This article aims to explore the views and responses of several Islamic organizations in Kebumen regarding childfree. This research uses qualitative methods (field research). The main object of this research is child-free practices and the views and responses of Islamic organizations in Kebumen. Data collection techniques were carried out by interviewing several Islamic organizations in Kebumen. Then the data analysis technique is descriptive analysis. The results of the study identified: (1) childfree as a phenomenon of current issues that reap various opinions, some support it and some don’t (2) childfree as a radical feminism. (3) childfree in the opinion of Islamic organizations in Kebumen regency such as (Nahdlatul Ulama, Muhamadiyah, Indonesian Islamic Da'wah Institute, and Hidayatullah) is that childfree has gone against nature, because it has deviated from the Qur’an, Hadis and the purpose of marriage.